2022
DOI: 10.3389/fvets.2022.1037880
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-150_R-1 mediates the HIF-1/ErbB signaling pathway to regulate the adhesion of endometrial epithelial cells in cows experiencing retained placenta

Abstract: Retained placenta (RP) refers to reproductive disorders caused by the failure of fetal membranes to be expelled 12 h after delivery in dairy cows. Postpartum adhesion of the fetal membranes to the uterus causes diseases such as mastitis or endometritis, which threatening the profitability of the dairy industry. Emerging evidence suggests that micro RNAs (miRNAs) play crucial roles in various processes, such as the occurrence and progression of fetal membranes discharge. However, the molecular mechanisms of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Twelve DE circRNAs were also randomly selected for qPCR validation, and the circRNA expression was consistent with the RNA-Seq data trend (Figure 1A-D and Table S4). Using previous research [1], the datasets of GSE214588 were downloaded from the Gene Expression Omnibus (GEO) (https://www.ncbi.nlm.nih.gov/gds/?term=, accessed on 18 October 2022), RNA-Seq data, and the biological characteristics of PCD were used to identify DE genes in these datasets. We focused on the involvement of DE miRNA target genes in apoptosis, cell differentiation, multicellular development, the positive regulation of cell surface and cell population proliferation, the negative regulation of cell apoptosis, chromatin, and the membrane (Figure 1E).…”
Section: Construction Of the Circamn1/mir-205_r-1/slc39a8 Signal Netw...mentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve DE circRNAs were also randomly selected for qPCR validation, and the circRNA expression was consistent with the RNA-Seq data trend (Figure 1A-D and Table S4). Using previous research [1], the datasets of GSE214588 were downloaded from the Gene Expression Omnibus (GEO) (https://www.ncbi.nlm.nih.gov/gds/?term=, accessed on 18 October 2022), RNA-Seq data, and the biological characteristics of PCD were used to identify DE genes in these datasets. We focused on the involvement of DE miRNA target genes in apoptosis, cell differentiation, multicellular development, the positive regulation of cell surface and cell population proliferation, the negative regulation of cell apoptosis, chromatin, and the membrane (Figure 1E).…”
Section: Construction Of the Circamn1/mir-205_r-1/slc39a8 Signal Netw...mentioning
confidence: 99%
“…The separation between the maternal and fetal placentas after fetal delivery is a prerequisite for the smooth expulsion of the placenta [1,2]. During the expulsion of the placenta, the ability to induce the proliferation, invasion, and migration of trophoblast and endometrial epithelial cells is weakened, increasing cell death and causing the fetal cotyledon to detach from the maternal uterine caruncle, thereby promoting placental expulsion [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with chronic endometritis, an increase in peri-implantation endometrial HIF-1α has been observed, which is a crucial trigger for the upregulation of VEGF, resulting in excessive endometrial vascularization and infertility [ 81 ]. The activation of the HIF-1 pathway also upregulates epidermal growth factor receptor and focal adhesion kinase, resulting in endometrial epithelial cells adhering to trophoblast cells and a retained placenta, triggering an inflammatory response [ 82 ]. In addition, in animal models with endometritis depending on the administration of lipopolysaccharide, Jiang et al [ 83 ] suggested a molecular mechanism involved in upregulating HIF-1α levels.…”
Section: Pathological Roles Of Endometrial Hif-1αmentioning
confidence: 99%
“…The sequencing result demonstrated the relationship between EPAS1 and retained placenta, and confirmed that EPAS1 was upregulated in the blood of cattle experiencing retained placenta. In addition, they found that EPAS1 was negatively regulated by miR-150_R-1, and then regulated the changes of related molecules in HIF-1/ErbB signaling pathway, especially the abnormal changes of EGFR and p-FAK, which affected the adhesion of fetal placental cotyledon to uterine nodules after delivery, leading to retained placenta ( 1 ).…”
mentioning
confidence: 99%